Book Reviews. (June 2016) - Petrova, Bilyana; Navia, Patricio; Niedzwiecki, Sara; Boniface, Dexter; Rosa‐Acosta, George; Vásquez, Manuel A.; Weitz‐Shapiro, Rebecca; Welp, Yanina; Garmany, Jeff; Weeks, Gregory
Abstract : Books reviewed in this issue. Daniela Campello, The Politics of Market Discipline in Latin America: Globalization and Democracy . New York: Cambridge University Press, 2015. Figures, tables, notes, bibliography, index, 239 pp.; hardcover 78.42, paperback 29.99, Kindle 98.40. Eduardo Dargent, Technocracy and Democracy in Latin America: The Experts Running Government . New York: Cambridge University Press, 2015. Tables, figures, bibliography, index. 216 pp.; hardcover 90, ebook 72. Ana Lorena De La O, Crafting Policies to End Poverty in Latin America: The Quiet Transformation . New York: Cambridge University Press, 2015. Figures, tables, bibliography, index, 194 pp.; hardcover 84.99, ebook 68. Jorge Heine and Brigitte Weiffen, 21st Century Democracy Promotion in the Americas: Standing Up for the Polity . New York: Routledge, 2015. Abbreviations, tables, bibliography, index, 196 pp.; hardcover 130, paperback 47. Juan Pablo Luna, Segmented Representation: Political Party Strategies in Unequal Democracies . New York: Oxford University Press, 2014. Tables, maps, figures, bibliography, indexes, 374 pp.; hardcover 115, ebook. Stephen Offutt, New Centers of Global Evangelicalism in Latin America and Africa . New York: Cambridge University Press, 2015. Map, tables, abbreviations, appendixes, bibliography, index, 192 pp.; hardcover 90, ebook 72. Mariela Szwarcberg, Mobilizing Poor Voters: Machine Politics, Clientelism, and Social Networks in Argentina . New York: Cambridge University Press. 2015. Figures, tables, maps, notes, bibliography, index, 185 pp.; hardcover 89.99, paperback 32.99, ebook 26. Brian Wampler, Activating Democracy in Brazil: Popular Participation, Social Justice, and Interlocking Institutions . Notre Dame: University of Notre Dame Press, 2015. Tables, figures, abbreviations, notes, bibliography, index, 312 pp.; paperback 39, pdf 39. Graham Denyer Willis, The Killing Consensus: Police, Organized Crime, and the Regulation of Life and Death in Urban Brazil . Berkeley: University of California Press, 2014. Tables, figures, notes, bibliography, index, 216 pp.; hardcover 70, paperback 29.95, ebook 29.95. Morris Morley and Chris McGillion, Reagan and Pinochet: The Struggle over U.S. Policy Toward Chile . New York: Cambridge University Press, 2015. Abbreviations, acronyms, bibliography, index, 354 pp.; hardcover 95, paperback 34.99, ebook 28.